Предмет: Алгебра,
автор: vladislawfedor
Помогите решить, спс заранее
Приложения:
Ответы
Автор ответа:
1
((a²-6a+9)/4)/((a-3)/12*1/(3-a))=((a-3)²/4)/((a-3)/12)*(1/(2*(3-a))=
=3*(a-3)*(1/(2*(3-a))=-3/2=-1,5. Ответ А).
=3*(a-3)*(1/(2*(3-a))=-3/2=-1,5. Ответ А).
Автор ответа:
1
Похожие вопросы
Предмет: Русский язык,
автор: prostinatanyap2ci3q
Предмет: Другие предметы,
автор: Аноним
Предмет: Українська мова,
автор: oksanasrtrlik31
Предмет: История,
автор: angelina18935
Предмет: Алгебра,
автор: aligator2718